Study of the ascorbic acid accumulation in Thymus L. genus species of Ukraine flora - Mazulin, O. V.; Steshenko, Ya. M.; Fukleva, L. A.; Mazulin, G. V.; Мазулін, Олександр Владиленович; Стешенко, Я. М.; Фуклева, Лариса Анатоліївна; Мазулін, Георгій Владиленович (Запорізький державний медико-фармацевтичний університет, 2024)
wild and cultivated species of the Thymus L. genus of Ukraine flora using thin layer chromatography (TLC) and spectrophotometry methods during vegetation season. Materials and methods. The research used herbs of four widespread wild and cultivated species of the Thymus L. genus of Ukraine flora during the growing season (June – August 2023). The presence and quantitative content of ascorbic acid were determined by TLC on a “Biostep” CD 60 densitometer (Germany) and spectrophotometry on a “Lambda 365” device (USA). Results. TLC and spectrophotometry methods were used to determine the presence and quantitative content of ascorbic acid in the herbs of four widespread Thymus L. genus species of Ukraine flora during the growing season. Accumulation of the compound was higher during flowering of cultivated species than wild plants. For the herbs Thymus vulgaris L. up to 39.10 ± 3.88 mg%; Th. x citriodorus (Pers.) Schreb. var. “Silver Queen” up to 36.19 ± 3.59 mg%. Мета роботи – за допомогою методів тонкошарової хроматографії (ТШХ) та спектрофотометрії визначити наявність і накопичення аскорбінової кислоти у траві чотирьох поширених дикорослих і культивованих видів роду Thymus L. флори України. Матеріали і методи. Для досліджень використали траву чотирьох поширених дикорослих і культивованих видів роду Thymus L. флори України під час вегетаційного періоду (червень – серпень 2023 р.). Наявність і кількісний вміст аскорбінової кислоти визначали методом ТШХ на денситометрі «Biostep» CD 60 (Німеччина) та спектрофотометрії на приладі «Lambda 365» (США). Результати. Методами ТШХ і спектрофотометрії встановлено наявність і кількісний вміст аскорбінової кислоти у траві чотирьох поширених видів роду Thymus L. флори України під час вегетації. Виявили, що накопичення сполуки найбільше під час цвітіння культивованих видів, ніж дикорослих. Для трави Th. vulgaris L. – до 39,10 ± 3,88 мг%; трави Th. x citriodorus (Pers.) Schreb. var. «Silver Queen» – до 36,19 ± 3,59 мг%.
Визначення накопичення аскорбінової кислоти у видах роду Thymus L. флори України
Mazulin O. V. - ORCID ID: 0000-0003-0628-4457; Steshenko Ya. M. - ORCID ID: 0000-0002-7538-6740; Fukleva L. A. - ORCID ID: 0000-0002-2930-0619; Mazulin G. V. - ORCID ID: 0000-0002-4227-7388.
Keywords: Thymus L. genus species; herb; thin layer chromatography; spectrophotometry; anti-inflammatory activity; antioxidant activity; regenerating activity; види роду чебрець; трава; тонкошарова хроматографія; спектрофотометрія; протизапальна активність; антиоксидантна активність; регенеруюча активність